ACTR-64. PHASE 2 STUDY OF SYM004 FOR ADULT PATIENTS WITH RECURRENT GLIOBLASTOMA (GBM). (6th November 2017) - Desjardins, Annick; Randazzo, Dina; Peters, Katherine B; Johnson, Margaret O; Massey, Woody; Herndon, James E; McSherry, Frances; Lipp, Eric S; Nadler, Paul; Horak, Ivan D; Friedman, Henry S
Abstract: BACKGROUND: Sym004, a recombinant antibody mixture binding specifically to the epidermal growth factor receptor (EGFR), contains two mouse-human chimeric IgG1 monoclonal antibodies (mAbs) binding to non-overlapping epitopes on the extracellular domain III of EGFR. It induces highly efficient internalization and degradation of EGFR on cancer cells. In solid tumors, the phase 2 Sym004 dose is 18 mg/kg intravenously every 2 weeks. Results of a phase 2 trial in recurrent GBM are reported. METHODS: Eligible patients are adults with recurrent GBM; EGFR amplified (>15% of cells exhibiting >5 copies of EGFR loci); ≤3 prior progressions; ≥4 weeks after chemotherapy, or study drug; ≥12 weeks after radiation; adequate organ function; and KPS ≥70%. Patients received Sym004 18 mg/kg IV every 2 weeks and imaging every 8 weeks. Bevacizumab naïve (cohort 1) and bevacizumab failure (cohort 2) patients were enrolled. RESULTS: As of 5/26/2017, 24 patients have been treated on study (cohort 1: 17 patients; cohort 2: 7 patients). Grade 3 or higher adverse events (AEs) possibly related to study include: fatigue (grade 3, n=1); skin infection (grade 3, n=1); hypokalemia (grade 3, n=1); and dry skin (grade 3, n=1). Adverse events of special interest are: rash (grade 3, n=3; grade 2, n=7; grade 1, n=12) and hypomagnesemia (grade 1, n=18). Eighteen patients experienced disease progression within 2 months of initiating treatment, but three patients remained stable for at least six months. CONCLUSION: Because of the low frequency of significant cutaneous toxicity and hypomagnesia observed in our phase 2 trial evaluating GBM patients, AEs generally associated with anti-tumor response to anti-EGFR mAbs, we are increasing the dose administered to 24 mg/kg to evaluate whether increased efficacy may be observed. Data on the new dose will be presented.